Green Architecture Concept Application on USU Kwala Bekala Library - Nasution, Achmad Delianur; Handiningtyas, Sharfina (Talenta Publisher, 2020)
The library is one of the building functions needed in the university's development standards. A library serves as a place to find information and collections as well as an educational recreation place. Not only providing facilities for the academic community, but Library also expected to be useful for all people, especially those in the surrounding area. For this reason, the supporting area of Science Techno Park which is an area for the development of economic and educational activities in USU ​​Kwala Bekala campus and its surroundings chooses Library as one of its facilities. In USU Kwala Bekala master plan, the location of Library is in the entrance zone with 16 Ha area. This zone is the gateway of USU Kwala Bekala area so the concept of